Pharmacological and resting state fMRI reveal Osteocalcin’s effects on mouse brain regions with high Gpr37 and Gpr158 expression - Freus, Natalia; Wank, Isabel; Häfele, Maximilian; Kalinichenko, Liubov; Müller, Christian P.; Strobelt, Sandra; Ludwig, Andreas; Heß, Andreas; Kreitz, Silke (Scientific Reports, 2025)
Osteocalcin (OCN) is an endocrine hormone that signals in the periphery, regulating male fertility, energy expenditure and glucose homeostasis. It can also cross the blood-brain-barrier and act on the brain via receptors GPR37 and GPR158. In the brain, OCN influences neurotransmitter synthesis of serotonin, norepinephrine, and dopamine. OCN’s function is related to cognitive and memory performance and lack of OCN is associated with anxiety and depression-like behavior in mice. We used multiparametric magnetic resonance imaging (MRI) including pharmacological MRI and resting state functional MRI, along with gene expression data for Gpr37 and Gpr158 to investigate the physiological effects of intravenously administered OCN on the wild type mouse brain. We found four core brain regions (brainstem, limbic output, association cortex, and basal ganglia) that are highly relevant in all three analytical modalities (i.e. pharmacological, resting state MRI and gene expression) and play therefore a major role in mediating OCN’s effect in the brain. This study provides the first imaging data of the physiological impact of OCN on the mouse brain, suggesting its potential role in modulating brain function and its relevance as a candidate for further investigation in anxiety, depression, and cognitive impairments.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Allen brain atlas; Depression; Functional connectivity; Mouse fMRI; Osteocalcin; rCBV